First Evidence of the Possible Influence of Avoiding Daily Liquid Intake from Plastic and Glass Beverage Bottles on Blood Pressure in Healthy Volunteers - Liesa Geppner; Sophie Grammatidis; Harald Wilfing; Maja Henjakovic (Microplastics)
The global microplastic pollution issue, as a result of the indispensable usage of microplastics in building materials, packaged food, medical products and consumer goods, poses significant health problems for the population. These small particles can penetrate intact cell barriers in the intestines and alveoli, thereby entering the bloodstream. The aim of this pilot study was to investigate the effects of reduced plastic consumption on blood pressure. Eight adult and healthy participants abstained from consuming commercially produced bottled beverages and restricted their primary fluid intake to tap water. Blood pressure was measured on both sides before, after 14 days and after 28 to 30 days of this partial plastic diet. Women exhibit a significant change in systolic blood pressure on the right arm after 2 and 4 weeks, while the left arm demonstrates no significant changes in blood pressure. On the contrary, in men, systolic blood pressure values on both arms show no significant alterations, attributable to the high variability across the three participants. Moreover, no significant differences in systolic blood pressure were observed when analysing the entire cohort. Significant findings are evident only at the two-week mark for diastolic blood pressure for all participants in both arms. When considering diastolic blood pressure separately for women and men, men again show no significant changes in blood pressure on either arm. However, women exhibit a significant decrease in diastolic blood pressure on the left arm after 2 weeks and a statistically significant decline in diastolic blood pressure on the right arm after both 2 and 4 weeks. The results of the study suggest, for the first time, that a reduction in plastic use could potentially lower blood pressure, probably due to the reduced volume of plastic particles in the bloodstream. To confirm this hypothesis, a larger sample of male and female participants must be examined, ideally with the monitoring of plastic concentration in the blood.